The Apostle Paul - Johnson, Luke Timothy; Teaching Company (Chantilly, VA : Teaching Co., 2001)
A series of twelve lectures examining St. Paul, his writings, and his message, presented by Luke Timothy Johnson, Professor of New Testament and Christian Origins at the Candler School of Theology, Emory University.
lecture 1. An apostle admired and despised -- lecture 2. How should we read Paul? -- lecture 3. Paul's life and letters -- lecture 4. Problems of early Christianity -- lecture 5. First and Second Thessalonians -- lecture 6. Life in the world : First Corinthians -- lecture 7. Life in Christ : Second Corinthians -- lecture 8. Life and law : Galatians -- lecture 9. Life and righteousness : Romans -- lecture 10. Fellowship : letters from captivity -- lecture 11. History and theology -- lecture 12. Paul's influence.
Lectures.
Lecturer, Luke Timothy Johnson.
Compact disc.
In container (23 cm.).
Keywords: Paul, -- the Apostle, Saint -- Teachings; Bible. -- Criticism, interpretation, etc; Audiobooks